Draft genome of ochrobactrum intermedium strain M86 isolated from non-ulcer dyspeptic individual from India - Kulkarni, Girish; Dhotre, Dhiraj; Dharne, Mahesh S.; Shetty, Sudarshan; Chowdhury, Somak; Misra, Vatsala; Misra, Sriprakash; Patole, Milind; Shouche, Yogesh (GUT Pathogens, 2013)
Background: Ochrobactrum intermedium is an emerging opportunistic pathogen of humans that is closely related to members of the genus Brucella. Earlier, we reported the case of an Indian subject with non-ulcer dyspeptic symptoms whose urease positive gastric biopsy revealed the presence of Helicobacter pylori along with non-Helicobacter like bacteria, eventually cultured and identified as O. intermedium strain M86. Results: Here, we describe the unclosed draft genome of the strain M86 with a length of 5,188,688 bp and mean G+C content of 57.9%. We have also identified many putative gene clusters that might be responsible for its persistence in the gastric mucosa. Comparative analysis of genomic features of Ochrobactrum intermedium strain M86 and Ochrobactrum intermedium LMG 3301(T) was also done. Conclusions: This paper attempts to gain whole-genome based insights into the putative gene determinants of O. intermedium for survival in the highly acidic stomach lumen environment. Identification of genes putatively involved in the various metabolic pathways may lead to a better understanding of the survival of O. intermdedium in acidic condition.

Genome sequencing analysis reveals virulence-related gene content of Ochrobactrum intermedium strain 229E, a urease-positive strain isolated from the human gastric niche - Kulkarni, Girish J.; Shetty, Sudarshan; Dharne, Mahesh S.; Shouche, Yogesh S. (Fems Microbiology Letters, 2014)
We report draft genome sequence of Ochrobactrum intermedium strain 229E concurrent with Helicobacter pylori in urease positive gastric biopsy of non-ulcer dyspeptic individual from Southern part of India. Since the role of Ochrobactrum in human gastric environment is poorly understood, comprehensive pathological, microbiological, and genome level understanding are necessary to evaluate its association with H. pylori in the gastric niche. Comparative analysis of O. intermedium 299E strain revealed functional similarities with virulence related gene clusters present in H. pylori genomes, which probably might aid in its ability to persist in the human gastric mucosa. However, H. pylori specific vacuolating cytotoxin (vacA) involved in vacuolization, cytotoxicity, and T-cell inhibition was absent in the O. intermedium 229E genome. Taken together, O. intermedium 229E shared numerous features like secretion system, urease, and flagella with H. pylori genome sequence that might aid concurrence in the gastric niche.
Keywords: Helicobacter pylori; Ochrobactrum intermedium strain 229E; virulence related gene clusters